Communication from the auditor of public accounts, in response to Senate resolution : January 5, 1865 (Document (Virginia. General Assembly. Senate), 1865)
December 20, 1864 Reply of the Auditor to Senate resolutions requesting a statement of the accounts of officers entitled to salaries and officers entitled to per diem compensation since April 17, 1861. Said reply was published as a Senate document in January 1865.